2017
DOI: 10.12927/hcq.2017.25075
|View full text |Cite
|
Sign up to set email alerts
|

BOOMR: Better Coordinated Cross-Sectoral Medication Reconciliation for Residential Care

Abstract: There is evidence that medication errors often arise during the transition of residents from acute care to long-term care (LTC) homes due to lapses in communication and documentation. Better Coordinated Cross-Sectoral Medication Reconciliation (BOOMR) is an integrated practice change improving medication safety during patient transitions through the health system. Our Medication Reconciliation (MedRec) redesign improved patient engagement using "the patient's story," increased quality of information, workflow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“… 22 30 31 Medication reconciliation was completed 2 days before hospital discharge to the nursing home in one study. 34 Six studies contacted the patient within the first week of discharge 25 27 29–31 33 and four in the second week. 17 22 23 26 In seven studies, pharmacists discussed outcomes of medication reconciliation with other team members such as the GP or nursing staff, 22 25 26 30–33 whereas in four a written report was produced for other clinical staff.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 22 30 31 Medication reconciliation was completed 2 days before hospital discharge to the nursing home in one study. 34 Six studies contacted the patient within the first week of discharge 25 27 29–31 33 and four in the second week. 17 22 23 26 In seven studies, pharmacists discussed outcomes of medication reconciliation with other team members such as the GP or nursing staff, 22 25 26 30–33 whereas in four a written report was produced for other clinical staff.…”
Section: Resultsmentioning
confidence: 99%
“… 22 Two studies reported that pharmacist completing medication reconciliation had the potential to free up clinical time for other healthcare team members. One reported that 2 hours of pharmacist time freed 3 hours of nursing time and 1 hour of physician time, 34 and the other stated that planned and unplanned physician visits were reduced. 28 Three studies reported the mean time taken to complete medication reconciliation by pharmacist.…”
Section: Resultsmentioning
confidence: 99%
“…An average of two discrepancies and six "clinical concerns" per patient were identified. 25 Neutral findings have been reported relating the impact of discrepancies identified per patient to medication errors 30 days after discharge to home. 12,26 No studies have been identified that reported negative findings, a factor likely resulting from publication bias.…”
Section: Satisfaction Amentioning
confidence: 99%
“…Many studies using structural or pharmacist-led interventions to identify and resolve medication discrepancies have been affected by the processes used to obtain the best possible medication history or the number of transition points involved. 12,14,15,25,[27][28][29][30] Heart Failure Medication Reconciliation Transitional Care Clinic. 31,32 Upon evaluating these and similar services, 50%-95% of patients had at least one discrepancy.…”
Section: Satisfaction Amentioning
confidence: 99%
“…the complexity of the healthcare system, in valuing and addressing both the adaptive and technical components in improving quality. Vuong et al (2017) demonstrate the potential of successful medication reconciliation to reduce costs and improve patient safety through their approach of tapping into the intrinsic motivators for change and creating a platform for the broad engagement through patient story, required in the redesign on this process. As well, additional cases presented in this edition: reducing length of stay in hip fracture patients by the Greater Toronto Area Rehabilitation Network (Levy et al 2017); improving discharge summaries in St. Thomas Elgin General Hospital (Sheridan et al 2017); and preventing 'error-based transfers' through improving advanced directives at William Osler Health System (Oliver and Chidwick 2017) provide excellent examples of utilizing the model for improvement as a means to engage those providing and receiving care to redesign and improve the quality of services provided.…”
Section: Quality Controlmentioning
confidence: 99%